2007
DOI: 10.1289/ehp.9821
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Ultrafine Carbon Black with Iron and Nickel on Heart Rate Variability in Spontaneously Hypertensive Rats

Abstract: BackgroundParticulate matter (PM) has been reported to be associated with alterations in heart rate variability (HRV); however, the results are inconsistent. We propose that different components of PM cause the discrepancy.ObjectiveIn this study, our goal was to determine whether different types of exposure would cause different HRV effects, and to verify the interactions between co-exposing components.MethodsUltrafine carbon black (ufCB; 14 nm; 415 μg and 830 μg), ferric sulfate [Fe2(SO4)3; 105 μg and 210 μg]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…This is consistent with the bulk of the both the epidemiological (e.g., Devlin et al, 2003) and toxicological (e.g., Chen and Hwang, 2005) literature, which reports lower HRV parameters associated with PM exposure. Furthermore, the 2-3-ms difference in SDNN between CAPs-and air-exposed SH rats is similar to exposure-related changes in rodents from other PM studies that were found to be statistically significant (Pham et al, 2009;Chang et al, 2007). We suspect that with more animals per group (presently n = 4) that differences in HRV would also have been significant in this study.…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with the bulk of the both the epidemiological (e.g., Devlin et al, 2003) and toxicological (e.g., Chen and Hwang, 2005) literature, which reports lower HRV parameters associated with PM exposure. Furthermore, the 2-3-ms difference in SDNN between CAPs-and air-exposed SH rats is similar to exposure-related changes in rodents from other PM studies that were found to be statistically significant (Pham et al, 2009;Chang et al, 2007). We suspect that with more animals per group (presently n = 4) that differences in HRV would also have been significant in this study.…”
Section: Discussionsupporting
confidence: 84%
“…371 In general, reductions in several measures of HRV have been shown. [372][373][374][375][376] Most of the recent research has focused on exploring the roles of susceptibility and exposure characteristics. Decreases in heart rate and HRV indices have been reported to be pronounced in senescent mice, which indicates that aging may be a susceptibility factor.…”
Section: Vascular Dysfunction and Atherosclerosismentioning
confidence: 99%
“…Black carbon (BC) from combustion sources is also considered an important indoor pollutant affecting people's health, and a World Health Organization report suggests that BC might be a particularly toxic component of PM . Animal experiments and epidemiological studies have demonstrated that BC levels are associated with changes in cardiac autonomic function by altering HRV indices . However, outdoor ambient PM is the focus of most research, and frequently, only a single‐size range of PM is considered.…”
Section: Introductionmentioning
confidence: 99%